(untitled) (Conferencea, 2023)
The article is concerned with the variants of representation of the binary opposition "friend/foe"; it is traced how its logical transformation into the triad "another - one’s own - a friend" takes place. The importance of the influence of the "place identity" on the emergence of the "psychological and moral" crisis of the hero Captain Scott, when nationally "us" becomes "strangers", is noted. Within the framework of the article, a complex of linguistic means was considered that actualize the opposition "friend/foe" and evaluative vocabulary and pronouns (we, us, our, they, you and I) were also analyzed.